Systems and breakdown of self-incompatibility. (4th May 2022) - Ahmad, Muhammad Husnain; Rao, Muhammad Junaid; Hu, Jianbing; Xu, Qiang; Liu, Chenchen; Cao, Zonghong; Larkin, Robert M.; Deng, Xiuxin; Bosch, Maurice; Chai, Lijun
Abstract: Self-incompatibility (SI) is a prezygotic mechanism that prevents self-pollination in flowering plants by distinguishing between nonself- and self-pollen. It controls sexual reproduction by promoting outcrossing and avoiding inbreeding. For thousands of years, this trait has been effectively exploited by breeders and growers as a tool to manipulate domesticated crops. However, efforts to spell out the molecular features of SI have begun only during the past thirty years. For breeders that need to produce homozygous lines, SI is undesirable. Moreover, in fruit crops, SI hinders the production of true to type plants and high-quality fruits with uniform traits because SI favors outcrossing. Numerous techniques have been developed to break down SI. Here, we review the current understanding of different molecular SI systems and pinpoint different physiological and molecular techniques used to break down SI. We also discuss evolutionary events that led to the transition from SI to self-compatibility (SC).